Impact of HLA-B27 and Disease Status on the Gut Microbiome of the Offspring of Ankylosing Spondylitis Patients - Matthew L. Stoll; Kimberly DeQuattro; Zhixiu Li; Henna Sawhney; Pamela F. Weiss; Peter A. Nigrovic; Tracey B. Wright; Kenneth Schikler; Barbara Edelheit; Casey D. Morrow; John D. Reveille; Matthew A. Brown; et al. (MDPI AG, 2022)
Multiple studies have shown the microbiota to be abnormal in patients with spondyloarthritis (SpA). The purpose of this study was to explore the genetic contributions of these microbiota abnormalities. We analyzed the impact of HLA-B27 on the microbiota of children at risk for SpA and compared the microbiota of HLA-B27+ pediatric offspring of ankylosing spondylitis (AS) patients with that of HLA-B27+ children with SpA. Human DNA was obtained from the offspring for determination of HLA-B27 status and polygenic risk score (PRS). Fecal specimens were collected from both groups for sequencing of the V4 region of the 16S ribosomal RNA gene. Among the offspring of AS patients, there was slight clustering by HLA-B27 status. After adjusting for multiple comparisons, five operational taxonomic units (OTUs) representing three unique taxa distinguished the HLA-B27+ from negative children: Blautia and Coprococcus were lower in the HLA-B27+ offspring, while Faecalibacterium prausnitzii was higher. HLA-B27+ offspring without arthritis were compared to children with treatment-naïve HLA-B27+ SpA. After adjustments, clustering by diagnosis was present. A total of 21 OTUs were significantly associated with diagnosis state, including Bacteroides (higher in SpA patients) and F. prausnitzii (higher in controls). Thus, our data confirmed associations with B. fragilis and F. prausnitzii with juvenile SpA, and also suggest that the mechanism by which HLA-B27 is associated with SpA may not involve alterations of the microbiota.